SEM Model to analyze the factors affecting university image: A study on International Islamic University Chittagong - Alam, Mohammad Manjur (IIUC Studies, 2022)
Private higher education institutions (PHEIs) have emerged as more competitive and stimulating day by day due to alternative accessibility and availability. University management ensures a global image to meet their stakeholders and social expectations. This study sets out to identify factors affecting university image by developing a structural equation model. A proposed model of overall university image formation through structural equation modeling, 310 respondents have been collected by using a five-point Likert scale questionnaire. Descriptive statistics, correlation, confirmatory factor analyses, and structural equation modeling were run to evaluate factors affecting overall image in IIUC. Based on the findings, all factors measured in this study have a positive significant effect on the overall university image. This research also explored that non-academic and management image is the most important predictors from the IIUC context. The model explains the overall university image well (61% of the total variation). This study is important for future marketing and better strategic plan to meet the needs of IIUC stakeholders as well as other HEIs in Bangladesh. IIUC Studies Vol.18, December 2021: 65-88